Characteristic of Older Adult with Balance Disorder in Rehabilitation Clinic Dr. Hasan Sadikin General Hospital 2014 - Yun, Ku Shi; Defi, Irma Ruslina; Dwipa, Lazuardhi (Althea Medical Journal, 2016)
Background: Older adult population is increasing worldwide. Balance has an important role in conducting daily activities and mobility, with impaired balance it can lead to negative impacts for example fall. This study is conducted to obtain common factors and characteristics of older adults with balance disorder to provide better rehabilitation services.Method: A descriptive study was conducted in the Physical Medicine and Rehabilitation Clinic of Dr. Hasan Sadikin General Hospital, Bandung from August-October 2014 using total sampling method and a 5 times sit-to-stand (5STS) test was conducted. The total sample obtained was 34.Result: The characteristics of older adult with balance disorder in this study were mostly from young old (n=17), male gender (n=19), and mean 5STS test is 18.48 seconds. Most of the patients had high blood pressure (n=29), normal body mass index (BMI) (n=22), independent activity of daily living (ADL) (n=21), and use of greater than 3 medication (n=21).The most common disease found is musculoskeletal disease and majority of patients had one medical disease.Conclusion: Older adults categorized as young old has the greatest frequency of having balance disorder. Increase in age, increases the duration of 5STS test conducted. The most common problem among older adult is high blood pressure, musculoskeletal disease and hypertension and majority of the patients consume greater than 3 medication. Lastly, most of the BMI and the ADL of the older adults were normal.Â DOI:Â 10.15850/amj.v3n1.718